The Effect of Low Impact Aerobic Exercise on Static Balance Levels of Elderly Women Medan Healthy Spirit Gymnastics Club 2023 - Dodi, Dodi Arianto; Anton, Anton Komaini (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the effect of gymnastic exercises aerobic low impact against ratestatic balance in elderly women at the Medan Senam Semangat Sehat Club in 2023. The problem in this study is that based on the results of observations and observations that have been made by researchers the level of static balance in elderly women is not normal. This research was conducted at the Medan Sunggal Healthy Spirit Gymnastics club. This study uses an experimental method by design none group pre-test dan post-test. The population is 41 people and the sample in this study is 11 elderly women in the Senam Semangat Sehat club. The sample is taken using a purposive sampling technique. Data analysis techniques using statistical analysis include normality tests, homogeneity test, and hypothesis testing. The results of data analysis from the influence of gymnastics aerobic low impact against ratestatic balance in elderly women in the Senam Semangat Sehat club. Obtained Count = 11.238 >ttable = 1.812 at the real level α = 0.05 and the difference in the average increase between the results pre-test 31.54 and post-test 36.27. Based on the research results that have been obtained by analyzing and testing the hypothesis, it can be concluded that there is a significant effect of gymnastic training aerobic low impact against ratestatic balance in elderly women at the Medan Senam Semangat Sehat Club in 2023.